Dynamic alterations of circulating lymphocytes during the trajectory of Hantaan virus-induced hemorrhagic fever with renal syndrome - Su, Lin; Liu, Shuangjuan; Shi, Lei; Cheng, Yuan; Gao, Juanjuan; Guo, Ruirui; He, Yinli; Zhang, Linpei; Chen, Tianyan; Hu, Jinsong; Li, Xiaojiao; Wang, Yawen (Frontiers in Immunology, 2025)
IntroductionHemorrhagic fever with renal syndrome (HFRS) is a zoonotic disease with high mortality. Almost 90% of global cases of HFRS are induced by Hantaan virus (HTNV) infection. Although lymphocyte dysfunction is a critical factor in HFRS progression, the specific immune dynamics of HTNV remain unexplored, and current analyses predominantly depend on single-time point sampling. Therefore, comprehensive longitudinal studies are needed to characterize circulating lymphocyte dynamics during HTNV-induced HFRS progression.MethodsIn this study, we conducted a flow cytometric analysis of circulating lymphocytes in 39 patients with HTNV-induced HFRS across different clinical phases. The analysis encompassed conventional T cells, unconventional T cells, B cells, NK cells and their respective repertoires.Results and DiscussionHere, we revealed phase-specific immune patterns: CD8+ T, CD8+ Tems, and activated CD8+ T, MAIT and NKT cells peaked during febrile/oliguric phases before declining in polyuria/recovery, while CD4+ T and MAIT cells showed inverse fluctuation patterns. Higher frequencies of CD8+ Tem, B, and CD56dim NK cells during the febrile phase correlated with severe disease, enabling early risk stratification. Lower CD4+ Tcm levels in the oliguric phase marked progression to severe HFRS, indicating potential therapeutic strategies aimed at enhancing CD4+ Tcm generation or inhibiting effector differentiation. Additionally, CD38 and CD161 expression predicted specific lymphocyte subset dynamics, offering novel biomarkers for immunomodulatory strategies. Our study thus provides the first comprehensive atlas of lymphocyte evolution in HTNV-induced HFRS, connecting immune dysregulation with clinical outcomes.